Antibacterial Activity of Leaf Extracts of Anredera cordifolia (Ten.) Steenis and Muntingia calabura L. Against Streptococcus pneumoniae - Nuke Annisa Nasution; I Made Artika; Dodi Safari (Current Biochemistry, 2020)
Antibacterial resistance in Streptococcus pneumoniae has been increasing and is one of ongoing global concern. The need to find new antibacterial agents against Streptococcus pneumoniae is of paramount importance. Medicinal plants are prospective sources of antibacterial agents. The aims of the present study were to determine the activity of leaf extraxt of Anredera cordifolia (Ten.) Steenis and Muntingia calabura L. against Streptococcus pneumoniae. Leaves of Anredera cordifolia (Ten.) Steenis were extracted using 96% ethanol, while the leaves of Muntingia calabura L were extracted using 100% methanol. The leaf extracts of the two plants obtained were bioassayed for antibacterial activity against Streptococcus pneumoniae ATCC 49619 and a clinical isolate Streptococcus pneumoniae PU 067. Results showed that leaf extracts of both Anredera cordifolia (Ten.) Steenis and Muntingia calabura L. have antibacterial activity in vitro against Streptococcus pneumoniae ATCC 49619 at crude extract concentrations of 25%, 50%, 75% and 100% (w/v). Both plants extracts showed strongest activity against S. pneumoniae ATCC 49619 at extract concentration of 75%. In addition, the extracts of both plants have inhibitory activity against growth of the clinical isolate Streptococcus pneumoniae PU 067. Both plant extracts showed strongest activity against S. pneumoniae PU 067 at extract concentration of 100%. Therefore, leaf extracts of Anredera cordifolia (Ten.) Steenis and Muntingia calabura L. can potentially be used as a source of antibacterial agent for Streptococcus pneumoniae. Keywords: Antibacterial agent, Anredera cordifolia (Ten.) Steenis, Muntingia calabura L., Streptococcus pneumoniae.